ANALISIS FAKTOR TERJADINYA STUNTING PADA SISWA KELAS 4 DAN 5 MADRASAH IBTIDAIYAH MUHAMMADIYAH SUKAJATI INDRAMAYU - Anisa Nur Fitriani; Kartini, Kartini (JOEL: Journal of Educational and Language Research, 2022)
According to World Health Organization (WHO), Chronic Nutrition Deficiency (Stunting) can influence cognitive or intelligence development, motoric development, and verbal development of children and cause not optimal development. Lack of nutrition impacts from children’s nutrition which is not fulfilled for a long period of time and it cannot be ignored because it can cause fatal effect on the children’s achievement and also their physical growth will be disturbed. There are some factors which cause stunting on children such as the food they consume, parents’ education, occupation, and others. This research aimed to find out the factors which cause stunting occurrence on students and to find out how was the impact of stunting on grade 4 and grade 5 students of Madrasah Ibtidaiyah Muhammadiyah Sukajati, Indramayu. This research was a qualitative research by using descriptive approach. The research samples were 7 grade 4 and 5 students of MI Muhammadiyah Sukajadi who experienced stunting. The research data were obtained from the interview with students, teachers, and students’ parents and students’ achievement were seen from the semester report scores. From the result of body height measurement according to TB/U at grade 4 and 5, there were 7 students experienced stunting at MI Muhammadiyah Sukajati. From the analysis result showed that the factors which cause stunting occurrence on students were grouped into two factors namely external factor and internal factor existed in the students and for the main factor of stunting occurrence was caused by internal factor in the students themselves who love to consume unhealthy food until it influences their nutrition status and influence their growth and development. And external factors such as occupation, education, and income of students’ parents also influence the thinking pattern of students to prepare a good nutrition intake for the children’s growth and development. Stunting is also an impact of low learning achievement owned by students and body height. Until the students experienced stunting obtain low achievement. Besides, low students’ achievement was also caused by another factor and not only stunting such as students’ learning motivation, students’ learning concentration, and the approach and also the attention from their parents.